TERAPI NON FARMAKOLOGI YANG BERPENGARUH TERHADAP KUALITAS TIDUR IBU HAMIL LITERATURE REVIEW - Luvi Anasari; Triatmi Andri Yanuarini; Lumastari Ajeng Wijayanti; Finta Isti Kundarti (Akademi Keperawatan Dharma Husada Kediri, 2022)
Introduction: Physical changes in pregnant women, one of which is a heavy burden on the stomach which results in changes in body posture that make pregnant women have to rest and sleep enough. Pregnant women who have poor sleep quality will have a negative impact on themselves and their fetuses, so they require appropriate treatment, one of which is non-pharmacological therapy that directly affects sleep quality. Method: This study consists of various types of non-pharmacological therapies which are discussed in detail in the form of a literature review. This literature study uses a systematic mapping study design with literature searches using the PubMed and Google Scholar databases in the 2015-2021 range using the keywords lavender, pregnancy exercise, yoga, massage, sleep hygiene, cognitive behavioral therapy, progressive muscle relaxation, sleep quality in pregnancy. using the Bolen operator method. Result: The search results found 13 journals that met the inclusion criteria. The method used to minimize bias is the selection of homogeneity in the research design (experiment). There is an effect of non-pharmacological therapy on the quality of sleep of pregnant women before and after the intervention with the most influential therapy, namely back massage, pregnancy exercise, sleep hygiene and the simplest therapy is lavender aromatherapy. Conclusion: All interventions can be applied to pregnant women to help improve their sleep quality, but giving back massage interventions, pregnancy exercises, sleep hygiene and lavender aromatherapy is recommended for pregnant women because they have a more significant effect and are easy to do Keywords: Non-pharmacological therapy, sleep quality of pregnant women